2021
DOI: 10.1016/j.chest.2021.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obesity in Critical Illness

Abstract: The prevalence of obesity is rising worldwide. Adipose tissue exerts anatomic and physiological effects with significant implications for critical illness. Changes in respiratory mechanics cause expiratory flow limitation, atelectasis, and V_/Q_ mismatch with resultant hypoxemia. Altered work of breathing and obesity hypoventilation syndrome may cause hypercapnia. Challenging mask ventilation and peri-intubation hypoxemia may complicate intubation. Patients with obesity are at increased risk of ARDS and should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 111 publications
0
49
0
3
Order By: Relevance
“…Only one study has examined physique in relation to body weight ( 2 ); it reported that transporting patients who weighed more than 65 kg involved a significantly increased risk of adverse events compared with transporting patients who weighed less than 65 kg (OR, 1.95 [1.30–2.94]). Physiologic changes such as decreased expiratory reserve and functional residual capacity make obese patients more prone to hypoxemia ( 14 ). Although body weight is directly related to transport difficulties, we examined BMI in this study because we believe that BMI influences changes in the physiologic status of patients more than body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study has examined physique in relation to body weight ( 2 ); it reported that transporting patients who weighed more than 65 kg involved a significantly increased risk of adverse events compared with transporting patients who weighed less than 65 kg (OR, 1.95 [1.30–2.94]). Physiologic changes such as decreased expiratory reserve and functional residual capacity make obese patients more prone to hypoxemia ( 14 ). Although body weight is directly related to transport difficulties, we examined BMI in this study because we believe that BMI influences changes in the physiologic status of patients more than body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed a strong association between obesity and pulmonary hypertension, a condition characterised by an increase in mean pulmonary arterial pressure [7]. Alterations in respiratory system mechanics caused by obesity include expiratory flow limitation, atelectasis, and V/Q mismatch (occurring when either the ventilation airflow or perfusion blood flow is impaired, limiting the primary lung function of delivering oxygen to the blood) with hypoxaemia, all of which have important implications in the context of critical illness [10]. Tidal volume is also slightly lower in obese individuals; however, there is no significant effect on residual volume (RV) or total lung capacity (TLC) [1].…”
Section: The Mechanical Effects and The Impact Of Obesity On Lung Fun...mentioning
confidence: 99%
“…The rise in the prevalence of obesity affects the epidemiology of pulmonary diseases. Several studies have demonstrated that susceptibility to respiratory infections and hospitalisation rates are higher in obese patients than healthy-weight subjects [1,2,[10][11][12]. Chronic inflammatory diseases of the respiratory system develop based on the understanding of obesity as a state of chronic inflammation [1,11,13].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is also associated with an increase in kidney mass but the effect on clearance is complex. Obesity, by itself is a risk factor for both chronic kidney disease and acute kidney injury and assessment of kidney function can be influenced by both assessment and indexing strategies [ 4 6 ]. Increases in clearance have been reported which could be due to the increase in renal blood flow [ 7 ].…”
Section: Introductionmentioning
confidence: 99%